Electrophoretic Carbon Nanotube Field Emission Layer for Plasma Display Panels - Liu, Qifa; Yang, Zhuoqing; Wang, Yan; Ding, Guifu (Nano-Micro Letters, 2012)
A carbon-nanotube (CNT) electrophoretic deposition (EPD) process has been developed to prepare a field emission layer in plasma display panels (PDP) for discharge voltage reduction. The CNT layer as a source of discharge priming electrons has been fabricated on the PDP front panel. The balling grinding, mix-acid treatment and EPD parameters have been investigated in order to obtain good uniformity and excellent field emission capability of CNT layer, in order to meet the specifications of CNTs in PDP cell. The measured turn-on field was around 1.1 V/μm in the field emission testing while the minimum sustaining voltage was decreased by 30∼40 V with the use of CNT layer in the discharge testing.